2019
DOI: 10.5664/jcsm.7960
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Association Between Respiratory Events and Reflux in Patients With Obstructive Sleep Apnea and Laryngopharyngeal Reflux

Abstract: The aim of the current study was to test the hypothesis that there is a temporal correlation between reflux episodes and respiratory events in patients with laryngopharyngeal reflux and obstructive sleep apnea. Methods: Adults with clinically diagnosed laryngopharyngeal reflux confirmed by two validated instruments (reflux symptom index ≥ 13 and reflux finding score ≥ 7) and obstructive sleep apnea (OSA) underwent full polysomnography with concomitant and synchronized multichannel intraluminal impedance-pH eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 38 publications
(58 reference statements)
0
28
0
Order By: Relevance
“…The association between pH study and PSG findings was investigated in many studies, 14‐20 which reported controversial results. Some authors observed that patients with severe OSAS had a significant higher number of nocturnal proximal or distal oesophageal events compared with patients with mild OSAS, 14,16,17 while others did not find any association between reflux and OSAS findings 15,18,19,21‐23 . The inconsistencies may result from methodological differences across studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The association between pH study and PSG findings was investigated in many studies, 14‐20 which reported controversial results. Some authors observed that patients with severe OSAS had a significant higher number of nocturnal proximal or distal oesophageal events compared with patients with mild OSAS, 14,16,17 while others did not find any association between reflux and OSAS findings 15,18,19,21‐23 . The inconsistencies may result from methodological differences across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors used dual‐ or triple‐probe pH monitoring to evaluate reflux events and did not consider non‐acid HREs 18,19 . Others only included patients with GERD (distal probe findings) 14,20,23 or oesophagitis 21 . Among studies reporting gastrointestinal findings, the prevalence of patients with GERD or GERD and LPR varied from 38.9% to 100% of cases 14,15,18,20,21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations